2012
DOI: 10.1182/blood-2011-10-388470
|View full text |Cite
|
Sign up to set email alerts
|

Patient age at diagnosis is associated with the molecular characteristics of diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma is the most frequent type of B-cell lymphoma in adult patients but also occurs in children. Patients are currently assigned to therapy regimens based on arbitrarily chosen age limits only (eg, 18 or 60 years) and not biologically justified limits. A total of 364 diffuse large B-cell lymphomas and related mature aggressive B-cell lymphomas other than Burkitt lymphoma from all age groups were analyzed by comprehensive molecular profiling. The probability of several biologic features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(118 citation statements)
references
References 34 publications
10
108
0
Order By: Relevance
“…Indeed, these 2 characteristics may be surrogates for disease biology. Klapper et al 26 reported that age at diagnosis of DLBCL correlated with the molecular profile with genetic alterations previously shown to confer a poor prognosis in DLBCL accumulating with age. These included, for example, ABC subtype, MYC or BCL2 expression, gains and translocations affecting the BCL6 locus, and other complex cytogenetic alterations.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, these 2 characteristics may be surrogates for disease biology. Klapper et al 26 reported that age at diagnosis of DLBCL correlated with the molecular profile with genetic alterations previously shown to confer a poor prognosis in DLBCL accumulating with age. These included, for example, ABC subtype, MYC or BCL2 expression, gains and translocations affecting the BCL6 locus, and other complex cytogenetic alterations.…”
Section: Discussionmentioning
confidence: 97%
“…[28][29][30][31] In adults, the outcome for patients with GCB disease is superior to that seen in patients with the ABC subtype. 1 In patients of all ages, relapsed disease offers a much worse prognosis, with second-line therapies able to salvage only a fraction of patients.…”
Section: Discussionmentioning
confidence: 99%
“…45 These findings are in agreement with recent data indicating that aging is an important determinant of lymphoma biology. 46 In an effort to explain the proportional increase of ABC DLBCL with age, Mareschal et al 45 speculated that either there is a change in B-cell population during aging or there is putative pathological specificity of EBV in elderly patients with DLBCL. Not BLOOD, 18 JULY 2013 x VOLUME 122, NUMBER 3 EBV-POSITIVE DLBCL OF THE ELDERLY 331 …”
Section: Immunophenotypementioning
confidence: 99%